2018
DOI: 10.15345/iojes.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Anxiety, Perceived Mathematics Self-efficacy and Learned Helplessness in Mathematics in Faculty of Education Students

Abstract: There are various factors influencing learning and academic achievement of individuals. These may be external factors which do not arise from the individual, or affective factors which are closely related with the individual. In this study, affective factors such as anxiety, self-efficacy, and learned helplessness which influence learning performance of prospective teachers in mathematics were investigated with respect to their various characteristics, the mediating effect of self-efficacy in the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
3
10
0
2
Order By: Relevance
“…By research conducted by (Ekawati, 2015) states that there is a strong influence of anxiety on learning outcomes. Subsequent research conducted by (Gürefe & Bakalım, 2018) also said that there was a negative correlation between mathematics anxiety and student academic achievement.…”
Section: Discussionmentioning
confidence: 97%
“…By research conducted by (Ekawati, 2015) states that there is a strong influence of anxiety on learning outcomes. Subsequent research conducted by (Gürefe & Bakalım, 2018) also said that there was a negative correlation between mathematics anxiety and student academic achievement.…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, pupils were unconcerned about their tasks since they thought they had the resources to finish them all. On the other hand, students who believe that they have mastered skills and completed difficult assignments typically have higher efficacy beliefs (Gürefe & Bakalım, 2018).…”
Section: Self-efficacymentioning
confidence: 99%
“…According to Halim et al (2021) & Reyes (2019), the younger generation of Malaysians still have a problem with mathematics, and nearly half of them are already experince anxiety. Gürefe & Bakalım (2018) found that individual use mathematics in two distinct ways in their daily life: they apply known formulas or procedures to solve standard problems, or they confront perplexing problems using conventional mathematical approaches (e.g., generalizing and simplifying; looking for patterns; reasoning by analogy; exploring specific cases; translating to another setting) (Hunter, 2017). Educators pay less attention to students' reasoning ability, or in other words, the methods used are less varied, which in turn, makes student motivation difficult, and students' learning patterns are simply memorized and mechanistic (Sukirwan et al, 2018).…”
mentioning
confidence: 99%
See 2 more Smart Citations